Successful Intravascular Ultrasound-Guided Transradial Coronary Intervention with a 4Fr Guiding Catheter - Yasuhiro Nakano; Kenji Sadamatsu (Case Reports in Cardiology)
Minimizing the catheter size can reduce vascular access complications and contrast dye usage in coronary angiography. The small diameter of the 4Fr guiding catheter has limited the use of several angioplasty devices such as intravascular ultrasound (IVUS) in the past. However, the combination of a novel IVUS catheter and a 0.010 guidewire makes it possible to perform IVUS-guided percutaneous coronary intervention (PCI) with a 4Fr guiding catheter. We herein report the case of a 51-year-old man with silent myocardial ischemia who underwent IVUS-guided transradial PCI with a 4Fr guiding catheter.